PROFITABILITAS PERUSAHAAN TERHADAP PRAKTIK PERATAAN LABA (INCOME SMOOTHING) PADA PERUSAHAAN MANUFAKTUR DI INDONESIA (Studi Empris pada Perusahaan Manufaktur yang Go Publik yang terdaftar di BEI periode 2013-2015) - Mike Kusuma Dewi (JURNAL PUNDI, 2017)
In earnings information companies can be used to assess the performance of management, and can also to estimate the risk in investing in a company. Investors often focus their attention on earnings information without seeing the procedures used to generate earnings information will encourage the company's management to take income smoothing action. Hopefully the information provided in the financial statements is valid information, relevant and reliable for users of financial statements. In reality there is no denying that there are still companies that indicate the practice of income smoothing.               The purpose of this study is to determine the effect of ROE and NPM on the practice of income smoothing on manufacturing entities that have Go Public listed on the Indonesia Stock Exchange This study used a sample of 35 business entities that have Go Public period           2013-2015. The research hypothesis used Multiple Regression Analysis using SPSS Ver.data processing tool 16. The test result showed that ROE and NPM there is no significant influence to earnings smoothing practice. And in fact until 2015 where the good economic conditions do not affect management to implement the practice of income smoothing. Key words : ROE, NPM, Income smoothing